STUDIES ON THE EVALUATION AND IDENTIFICATION OF SILKWORM BREEDS OF BOMBYX MOR. L. WITH REFERENCE TO COCOON FLAMENT TRAITS - KUMAR, C.M. KISHOR; BASAVARAJA, H.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The process of silkworm breeding starts with examination of genetic resources and selection of breeding materials. In the present study, 8 dumbbell breeds were evaluated to know their genetic variability with regard to the yield characters giving thrust on post cocoon traits. The statistical results revealed that all the experimental breeds viz., CSR4, CSR5, CSR6, CSR 17, CSR19, 5HT, NB4D2 and NB 18 performed significantly different indicating the presence of inherent variations. Multiple trait evaluation index study on the overall performance revealed that, CSR4, CSR5 and CSR 19 with 659.7. 596.8 & 595.7 cumulative indices respectively were ranked as top 3 breeds. Since the raw silk is composed of many filaments, variations in thickness of the individual filaments influence the raw silk deviation and thereby silk quality. Denier variation studies revealed that, the cocoon filament size showed marked variations with respect to cocoon layers. The denier curve reduces linearly in breeds CSR 19, CSR5 and CSR4 by recording higher regression co-efficient (slope-b) values of -0.00 127, -0.00129 and -0.001.36 respectively. Significant correlations were observed for size variation versus average filament size (r = - 0.6908*), maximum filament size (r = -0.8724**) and size differential (r = -0.9574***). Based on these results CSR4, CSR5 and CSR 19 have been identified as future breeding resource materials for development of breeds that can produce high quality silk of international standard.